1991
DOI: 10.1007/bf01541846
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and heterosexual anal intercourse

Abstract: Heterosexual anal intercourse is rarely discussed in the scientific literature. Review of the literature suggests the silence is linked to ethnocentric discomfort about it among researchers and health care providers, coupled with the misconception that anal sex is a homosexual male practice, not heterosexual. Review of surveys of sexual practices suggest that heterosexual anal intercourse is far more common than generally realized, more than 10% of American women and their male consorts engaging in the act wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 121 publications
2
33
0
Order By: Relevance
“…It can be hypothesized that younger women may engage more in anal sex than older women as an alternative to birth control, especially in low-income areas with fewer resources. Alternatively, they may engage in anal sex as frequently as older women but are more willing to report this activity, while older women may report having anal sex less due to taboos associated with HAS (Voeller, 1991).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It can be hypothesized that younger women may engage more in anal sex than older women as an alternative to birth control, especially in low-income areas with fewer resources. Alternatively, they may engage in anal sex as frequently as older women but are more willing to report this activity, while older women may report having anal sex less due to taboos associated with HAS (Voeller, 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Thirty-five percent of women and 40% of men aged 25-44 reported ever having heterosexual anal sex (HAS) (Mosher, Chandra, Jones, & Division of Vital Statistics, 2002). Anal sex carries a greater risk for women than vaginal intercourse (Misegades et al 2001;Voeller, 1991) with respect to HIV transmission, yet research has found that women underestimate the risks of anal sex (Halperin, 1999), and are less likely to use condoms during anal intercourse than vaginal intercourse (Misegades & Page-Shafer, 2001;Solorio, Milburn, Rotheram-Borus, Higgins, & Gelberg, 2006). In fact, seven times more women than homosexual men engage in unprotected receptive anal sex (Halperin).…”
Section: Introductionmentioning
confidence: 96%
“…The similarity of these reasons to the ones for not using condoms for vaginal sex underscores the predominance of pregnancy prevention over STD protection concerns in the college student population. For women, anal sex is a higher risk behavior for transmission of HIV than vaginal sex (Voeller, 1991). If college students were concerned about becoming infected with HIV/STD, they would prioritize the use of condoms for anal sex.…”
Section: Discussionmentioning
confidence: 99%
“…33 Consideration of such findings should also take into account that this highly stigmatized behavior is likely to be substantially underreported in surveys. [34][35][36] In a 1994 study of 354 MSM in Santo Domingo, only 22% of the interviewees self-identified as being ''homosexual,'' with over half self-identifying as ''heterosexuals'' (among whom HIV prevalence was 8%). 19 One of the main reasons that MSM tend to have much higher HIV prevalence than the general population is the unusually high risk of receptive anal intercourse, which is estimated to be 10-20 times riskier, per act, than receptive vaginal intercourse.…”
Section: Changes In Sexual Behaviormentioning
confidence: 99%